A tale of two red lines: Managing foreign policy crises in the Obama and Trump administrations. Issue 1 (2nd January 2021) - Da Vinha, Luis
Abstract: International crises emphasize the critical role that presidents and their advisory systems play in formulating and implementing foreign policy. Scholarly research has identified three distinct conceptual models of how presidents manage their decision-making systems – the competitive, formalistic, and collegial models. This article examines how Presidents Barack Obama and Donald Trump managed their advisory systems and formulated their policies toward Syria after the Assad regime employed chemical weapons against its people. The case studies demonstrate that each president employed a different approach to the decision-making processes, which significantly influenced the U.S. response to Syria's use of chemical weapons.